The role of autophagy in the treatment of type II diabetes and its complications: a review - Zhao, Xuan; Bie, Lu-Yao; Pang, Dao-Ran; Li, Xiao; Yang, Long-Fei; Chen, Dan-Dan; Wang, Yue-Rui; Gao, Yan (Frontiers in Endocrinology, 2023)
Type II diabetes mellitus (T2DM) is a chronic metabolic disease characterized by prolonged hyperglycemia and insulin resistance (IR). Its incidence is increasing annually, posing a significant threat to human life and health. Consequently, there is an urgent requirement to discover effective drugs and investigate the pathogenesis of T2DM. Autophagy plays a crucial role in maintaining normal islet structure. However, in a state of high glucose, autophagy is inhibited, resulting in impaired islet function, insulin resistance, and complications. Studies have shown that modulating autophagy through activation or inhibition can have a positive impact on the treatment of T2DM and its complications. However, it is important to note that the specific regulatory mechanisms vary depending on the target organ. This review explores the role of autophagy in the pathogenesis of T2DM, taking into account both genetic and external factors. It also provides a summary of reported chemical drugs and traditional Chinese medicine that target the autophagic pathway for the treatment of T2DM and its complications.